CREATING VISUAL ASSETS OF KOREAN VOCABULARY CARD GAME NOLJA - Maharani, Satyaning (VCD, 2021)
The Korean vocabulary card game Nolja is a game designed to assist the learning process of Korean vocabulary in an interactive way and suitable for women aged 15-25 years. However, as a new game, Nolja has a fatal problem with its design, namely, the placement of illustrations on the player card which makes the game finish too quickly, there are no tools to assess language proficiency on the card, the typeface on the card is less legible, and strokes on the illustration are too thin, Therefore, it is necessary to design a visual asset for the Nolja vocabulary card game. Visual asset design for Nolja includes game theme design, illustration, educational game system, layout, and content arrangement. This design aims to produce a Nolja card game design that is interactive, educational, and suitable for women aged 15-25 years who have the motivation and function to convey Korean language subject matter well. The design is carried out by qualitative methods through interviews with experts and extreme users in the game and learning the Korean language, distributing surveys to 100 target markets. This design is also supported by data collection from literature studies from books, journals, and articles from the Internet. The design produces a visual asset for the Nolja vocabulary card game with a stronger educational game system and a design style that matches the target market’s wishes so that it can be well received by the market. Keyword: Korean language, Visual learning media, Flashcards, Picture card games, Visual assets.